Biomass Derived Chemicals: Furfural Oxidative Esterification to Methyl-2-furoate over Gold Catalysts - Manzoli, Maela; Menegazzo, Federica; Signoretto, Michela; Marchese, Damiano (Catalysts, 2016)
The use of heterogeneous catalysis to upgrade biomass wastes coming from lignocellulose into higher value-added chemicals is one of the most explored subjects in the prospective vision of bio-refinery. In this frame, a lot of interest has been driven towards biomass-derived building block molecules, such as furfural. Gold supported catalysts have been successfully proven to be highly active and selective in the furfural oxidative esterification to methyl-2-furoate under mild conditions by employing oxygen as benign oxidant. Particular attention has been given to the studies in which the reaction occurs even without base as co-catalyst, which would lead to a more green and economically advantageous process. The Au catalysts are also stable and quite easily recovered and represent a feasible and promising route to efficiently convert furfural to methyl-2-furoate to be scaled up at industrial level.